Isolation of bioactive compounds from lichen Parmelia sulcata and evaluation of antimicrobial property - Arumugam Dhanesh Gandhi; Katike Umamahesh; Sivaji Sathiyaraj; Gunasekaran Suriyakala; Rajendran Velmurugan; Dunia A. Al Farraj; Mohamed Ragab Abdel Gawwad; Kadarkarai Murugan; Ranganathan Babujanarthanam; R. Saranya (Elsevier, 2022)
Background: Lichens were used as an ailment in the traditional medicine for treating various disorders for centuries. Since there is less evidence in the literature about the medicinal property of Parmelia sulcata (P. sulcata), we made a pioneer attempt to explore the antioxidant and antimicrobial properties of lichens. Methods: In the present study, the three Samples were collected by using the column chromatography by elucidating the ethyl acetate extract of P. sulcata, and the samples were subjected to DPPH and ABTS assays to find the free radical scavenging activity, total phenols and flavonoids were estimated. The minimum inhibitory concentration was evaluated against the bacterial species (Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumoniae) and fungal species (Candida albicans and Aspergillus fumigatus) by the microdilution method. The best activity sample was analyzed using the Gas Chromatography-Mass Spectrometry (GC-MS), Fourier Transmission Infrared Spectroscopy (FT-IR) and Nuclear Magnetic Resonance (NMR). Results: The results shown that all the samples contain phenols and flavonoids which are responsible for antioxidants, antibacterial and antifungal activities. Among that sample-3 shown best antimicrobial activity and it was analyzed and identified as 7-hydroxy-3-(2-methylbut-3-en2-yl)-chromen-2-one. Conclusion: The outcome of the study suggests that sample-3 shown good antimicrobial activity and identified as 7-hydroxy-3-(2-methylbut-3-en2-yl)-chromen-2-one. It can be a resource for further studies.